Socioeconomic determinants of stay-at-home policies during the first COVID-19 wave - Valgañón, Pablo; Lería, Unai; Soriano-Paños, David; Gómez-Gardeñes, Jesús (Frontiers in Public Health, 2023)
The COVID-19 pandemic has had a significant impact on public health and social systems worldwide. This study aims to evaluate the efficacy of various policies and restrictions implemented by different countries to control the spread of the virus. To this aim, we use a compartmental model to quantify the "social permeability" of a population, which reflects the inability of individuals to remain in confinement and continue social mixing allowing the spread of the virus. After calibrating the model to data corresponding to 42 countries, our results show that low-income countries have a harder time slowing the advance of the pandemic, even if the virus did not initially propagate as fast as in wealthier countries. Our study highlights the disparities between countries in their ability to mitigate the spread of the disease and the impact on vulnerable populations. This research contributes to a better understanding of the socioeconomic and environmental factors that contribute to the spread of the virus and the need for equitable policy measures to address the disparities in the global response to the pandemic.